Unsur Estetika Dalam Perancangan Media Pembelajaran Berbasis Karakter Untuk Mata Pelajaran TIK Siswa Sekolah Dasar (SD) - Sri Huning Anwariningsih (JURNAL GAUNG INFORMATIKA, 2011)
Learning media can help teacher to convey the intent of teaching learning materials. Development of instructional media should take attention to several aspects: usercharacteristics, aspects of software quality, design aspects that include linkages to the curriculum, and the aspect of visual communication. As part of visual communication,the aesthetic aspects should also be considered. Aesthetics is related to the harmonization of all the elements of art affect the feelings or emotions that learningmedia users. This paper reviewed the elements of aesthetic aspect which must be considered ini design of learning media.